230k views
0 votes
F(x) = -3x-3 g(x) =2x^3+2
Find f(6) and g(-3)

User Sinoroc
by
5.5k points

1 Answer

2 votes

Answer:


f(6)=-21\\\\g(-3)=-52

Explanation:

When given the following two functions,


f(x) =-3x-3\\g(x)=2x^3+2

One is asked to evaluate the functions for, (f(6)) and (g(-3)). One can do this by substituting the values (6) into the function (f) and (-3) into the function (g). These values will replace the parameter (x).


f(6)=-3(6)-3\\

Simplify,


f(6)=-18-3\\f(6)=-21

Now repeat this process for the guncion (g(x)) to evaluate for (g(-3))


g(-3)=2(-3)^3+2

Simplify,


g(-3)=2(-27)+2\\g(-3)=-54+2\\g(-3)=-52

User Boris Zbarsky
by
4.3k points